KILAU UMP Volunteers join Baling Post Flood Volunteer Mission - Mimi Rabita, Abdul Wahit (UMPSA, 2022)
BALING, 8 July 2022 – A total of 25 KILAU UMP volunteers participated in the Postflood Care Assistance Mission in Baling by carrying out cleaning activities at two houses in Kampung Bendang Pecah, Baling Kedah which were badly affected by the flood.